Across the worlds of Islam: Muslim identities, beliefs, and practices from Asia to America - Curtis, Edward E. (Columbia University Press, 2023)
"Unlike the majority of introductions to Islam, which all too often elide essential theological and legal debates in favor of presenting a homogenized Middle East-centric view of what Islam represents to all Muslims, this book provides a balanced perspective on Sunni, Shia, and Sufi Islam at the geographic, social, political, embodied, reproductive, and doctrinal margins. Its objective is to develop an inclusive vision of the religion and its many interrelated communities. By paying attention to the values, stories, and practices that characterize Muslim life across sectarian division we are able to render a nuanced portrait that transcends debates about orthodoxy and normativity and gives us more encompassing and accurate views of the forms that Islam takes and how Muslims think and act socially, culturally, theologically, and politically. It becomes apparent that inhabitants of regions beyond the Middle East are not heretics or infidels but rather central to the past, present, and future of the Muslim world. Chapter authors were commissioned by the editor specifically for the book. They include Farah Bakaari (English, Cornell) writing on Islam and its others, Michael Muhammad Knight (novelist and journalist, Philosophy, Central Florida) on rethinking the center of Islam, Tess Waggoner (Near Eastern Studies, NYU) on Turkish Alevi Ashiks, Holly Donahue Singh (Anthropology, Honors College, South Florida) on the ethical practices of Indian Muslim women, Henry Brill (policymaker, History, Georgetown) on 16th-century Mongol Sufi scholar Mirza Muhammad Haydar Dughlat, Kathryn Blanchard (Religious Studies, Alma) on teaching Islam as a non-Muslim, and Curtis himself on Elijah Muhammad, the Nation of Islam, and Black liberation, among others"--